Odpowiedź :
a) (x+√5)(x-√5)=x²-x√5+x√5-√25=x²-5
b) (2y-√3)(y+1)=2y²+2y-y√3+√3
c) (a+√2)(a-√3)=a²-a√3+a√2-√6=a²-a-√6
d) (2 √2+k)+(√2-k) =2√4-2k√2+k√2-k²=2×2-k√2-k²=4-k√2-k²
b) (2y-√3)(y+1)=2y²+2y-y√3+√3
c) (a+√2)(a-√3)=a²-a√3+a√2-√6=a²-a-√6
d) (2 √2+k)+(√2-k) =2√4-2k√2+k√2-k²=2×2-k√2-k²=4-k√2-k²
a) (x+√5)(x-√5)=x²-x√5+x√5-√25=x²-5
b) (2y-√3)(y+1)=2y²+2y-y√3+√3
c) (a+√2)(a-√3)=a²-a√3+a√2-√6=a²-a-√6
d) (2 √2+k)+(√2-k) =2√4-2k√2+k√2-k²=2×2-k√2-k²=4-k√2-k²
b) (2y-√3)(y+1)=2y²+2y-y√3+√3
c) (a+√2)(a-√3)=a²-a√3+a√2-√6=a²-a-√6
d) (2 √2+k)+(√2-k) =2√4-2k√2+k√2-k²=2×2-k√2-k²=4-k√2-k²